Social Theology in the Context of Modern Social Change: A Theological and Sociological Perspective - Saliareng, Riandli; Birahim, Grace Natalia (PARADOSI: Jurnal Teologi Praktika, 2024)
This paper delves into the complex relationship between theology and modern social change, particularly focusing on the responses of religious traditions, specifically Christianity, to evolving socio-cultural contexts. It begins by examining how technological advancements, demographic shifts, and globalization have reshaped religious practices and societal norms. The impact of these changes on religious institutions is significant, as they navigate the tensions between tradition and innovation. By employing sociological theories of change, such as those proposed by Ogburn and Davis, the paper highlights how institutions are adapting to material and immaterial elements of culture, responding to challenges like urbanization, aging populations, and shifts in family structures. It also explores the role of technology in both facilitating religious engagement and raising concerns over its potential to dilute spiritual experiences. Furthermore, the paper discusses key theological frameworks, including liberation theology and ecological theology, and their efforts to address social justice, inequality, and environmental crises. The role of Christianity in promoting social justice, reconciliation, and environmental stewardship is emphasized as a vital response to modern social challenges. Theological perspectives are positioned as essential for navigating complex issues such as climate change, economic inequality, and migration. The article concludes that theology, particularly social theology, must continue to evolve to provide moral and ethical guidance, helping communities and institutions respond to the pressing challenges of modern society.